Compact light-receiving system based on simulation of the light-receiving characteristics of a plant shoot - Obara, Shin'ya; Kawae, Osamu; Adachi, Takuya (Solar Energy, 2017)
•The plant light-receiving configuration is optimized on the solar trajectory of the habitat region.•The occupation area of a light-receiving system with a ginkgo tree is smaller than the flat plate.•The energy density of a light-receiving system with a plant shoot is advantageous. Many plants are dependent on carbohydrates obtained by photosynthesis for energy. Therefore, in a forest with many competitors, it is thought that the leaf shape, as well as the arrangement and orientation of many plants, are designed so as to maximize the photosynthetic rate. The shoot configuration of a photosynthetic plant evolves through space competition for sunlight. Therefore, a photosynthetic plant may have a high light-receiving density. This configuration can be applied to design a fine light-receiving system. In this paper, the configuration of the plant shoot is optimized for maximizing the light-receiving quantity by combining the Light Received Analysis Algorithm of a Plant Shoot (LAPS) with the L-System. The plant shoot consists of a branch and its leaf. In the present study, we propose an analytical method for investigating the relationships between the plant shoot configuration and the light-receiving characteristics of the plant, the local characteristics of the light-receiving system and plant shoot, the branching structure and the light-receiving density, and the optimal configuration of the light-receiving module and the ginkgo tree shoot configuration. Although the plant’s light-receiving configuration is optimized by the solar trajectory of the natural growth area, the plant shoot configuration depends on other factors besides light-receiving quantity. The occupation area of the light-receiving system with a ginkgo tree shoot is between 16% and 40% of that of the flat light-receiving system. The study results reveal the advantages of the light-receiving system with a plant shoot.